SOSIALISASI PEMBUATAN SUSU KELOR PROBIOTIK SEBAGAI PANGAN FUNGSIONAL - Aini Aini; Alfi Maulana; Siti Zaitun (Politeknik Medica Farma Husada Mataram, 2023)
Gempur Senior School is a group of seniors who follow learning activities. The elderly group is also active in other activities such as gardening. The activities carried out by the elderly school is in the gardening producing cane crops that have been sold all this time in the form of vegetables. This dedication is aimed at socializing the method of making probiotic milk or